Vaccination recommendations for the adult immunosuppressed patient: A systematic review and comprehensive field synopsis. (June 2017) - Lopez, Anthony; Mariette, Xavier; Bachelez, Hervé; Belot, Alexandre; Bonnotte, Bernard; Hachulla, Eric; Lahfa, Morad; Lortholary, Olivier; Loulergue, Pierre; Paul, Stéphane; Roblin, Xavier; Sibilia, Jean; et al.
Abstract: Background: Immunosuppressed patients are at risk of severe viral infections-related complications. National and international vaccination guidelines have been developed to decrease the mortality risk associated with these infections. However, a summary of these guidelines and the value of immunisation in this population is missing. Objectives: To summarize specific guidelines regarding vaccination in immunosuppressed patients. Methods: We performed a literature search based on last update vaccine guidelines in immunosuppressed adult patients published between 1/1/2005–1/31/2016 in English or French language using PubMed, Cochrane and Embase, as well as relevant medical society websites. Results: Of the 389 citations identified, 12 guidelines were selected Three additional guidelines were selected by searching on the websites from medical societies of each specialty. 15 guidelines were included, involving 19 medical societies issued from the US (n = 6), international collaboration (n = 3), UK (n = 2), Canada (n = 1), Australia (n = 1), France (n = 1), and Germany (n = 1). These guidelines provide recommendations on vaccination in asplenic patients (n = 5), cancer patients (n = 4), HIV patients (n = 5), hematopoietic stem cell recipients (n = 4), inflammatory bowel diseases patients (n = 5), psoriasis patients (n = 4), primary immunocompromised patients (n = 3), inflammatory rheumatic diseases patients (n = 6), and solid organ transplant recipients (n = 5). All guidelines recommended pneumococcal and injectable influenza vaccines. Other inactivated vaccines were recommended only in high risk patients. Live vaccines were usually contraindicated in patients under immunosuppressive therapy and/or in HIV patients with a CD4 count under 200/mm 3 . Conclusion: Pneumococcal and injectable influenza are the two essential vaccines recommended in all immunocompromised patients. Other inactivated vaccines are only indicated in high risk patients. Live vaccines are usually contraindicated. Highlights: Pneumococcal and injectable influenza are the only two vaccines universally recommended in all cases of immunosuppression. Other inactivated vaccines are not universally recommended, but only indicated in high risk patients. Live vaccines are contraindicated in patients under immunosuppressive therapy or in HIV patients with CD4 cells <200/mm 3 .